Lithium-ion battery
Patent Information
- Application Number
- JP2023141334
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-08-31
AI Technical Summary
【0010】 本開示によれば、充電時の膨張が小さいシリコンクラスレート電極活物質を含むリチウムイオン電池を提供することができる。
Smart Images

Figure 2025034751000001_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a lithium ion battery.
Background Art
[0002] In recent years, battery development has been actively carried out. For example, in the automotive industry, the development of batteries used in electric vehicles or hybrid vehicles has been promoted. Also, silicon is known as an electrode active material used in batteries, particularly lithium ion batteries.
[0003] Silicon electrode active materials have a large theoretical capacity and are effective for increasing the energy density of batteries. On the other hand, silicon electrode active materials have a problem of large expansion during charging. In contrast, it is known to suppress the expansion during charging by using a silicon class rate electrode active material as the silicon electrode active material.
[0004] For example, Patent Document 1 discloses a silicon class rate electrode active material having a silicon class rate type II crystal phase, having voids inside primary particles, and having a void volume of voids with a pore diameter of 100 nm or less of 0.05 cc / g or more and 0.15 cc / g or less.
[0005] x Si 136 (1.98 < x < 2.54), and discloses a silicon class rate electrode active material having a composition of.
Prior Art Documents
Patent Documents
[0006]
Patent Document 1
Patent Document 2
Summary of the Invention
[0007] Although silicon clathrate electrode active materials can suppress expansion during charging as compared with ordinary silicon electrode active materials, there is a demand for further suppression of the expansion of silicon clathrate electrode active materials during charging.
[0008] The present disclosure aims to provide a lithium-ion battery including a silicon clathrate electrode active material that exhibits low expansion during charging. [Means for solving the problem]
[0009] The present inventors have found that the above problems can be solved by the following means. <Aspect 1> An electrode active material layer is provided, The thickness of the electrode active material layer is 55 μm or less, the electrode active material layer comprises a silicon clathrate electrode active material; and The following relationship is satisfied: Lithium-ion battery: (Thickness of the electrode active material layer (μm)) 2 × (charge amount (mAh / g) of the silicon clathrate electrode active material)≦2,000,000 … (A). <Aspect 2> 2. The lithium ion battery of claim 1, wherein the electrode active material layer has a thickness of 35 μm or less. <Aspect 3> 3. The lithium ion battery of claim 1 or 2, wherein the charge capacity of the silicon clathrate electrode active material is 700 mAh / g or more and 3,500 mAh / g or less. Effect of the Invention
[0010] According to the present disclosure, it is possible to provide a lithium ion battery including a silicon clathrate electrode active material that exhibits small expansion during charging. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a graph showing the relationship between the value of (thickness (μm) of the electrode active material layer)2×(charge amount (mAh / g) of the silicon clathrate electrode active material) and the increase in confining pressure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.
[0013] Lithium-ion battery The lithium ion battery of the present disclosure has an electrode active material layer. The thickness of the electrode active material layer is 55 μm or less. The electrode active material layer includes a silicon clathrate electrode active material. The lithium ion battery of the present disclosure satisfies the following relationship: (Thickness of the electrode active material layer (μm)) 2 × (charge amount (mAh / g) of the silicon clathrate electrode active material)≦2,000,000 … (A).
[0014] The present inventors have found that when the electrode active material layer has a thickness of 55 μm or less and contains a silicon clathrate electrode active material, the expansion of the battery can be suppressed. Although not intending to be bound by any theory, the reason for this is presumed to be as follows. That is, since the silicon clathrate electrode active material is highly sensitive to reaction unevenness, it is believed that the expansion suppression effect is reduced when the reaction unevenness is large. In contrast, it is believed that by reducing the thickness of the electrode active material layer, the reaction unevenness can be suppressed, and as a result, the expansion can be efficiently suppressed.
[0015] In addition, the present inventors have found that in a battery containing a silicon clathrate electrode active material, an increase in the thickness of the electrode active material layer significantly affects the variation in the amount of battery expansion. That is, the amount of battery expansion increases with an increase in the amount of charge, but by satisfying formula (A), it has been found that the expansion of the battery can be suppressed even if the amount of charge is increased to a certain extent.
[0016] The lithium ion battery of the present disclosure may be a liquid battery or a solid-state battery. In the present disclosure, a "solid-state battery" refers to a battery that uses at least a solid electrolyte as an electrolyte, and therefore a solid-state battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. The solid-state battery of the present disclosure may also be an all-solid-state battery, i.e., a battery that uses only a solid electrolyte as an electrolyte.
[0017] The lithium ion battery of the present disclosure can be restrained from both sides of the stacking direction of each of the layers by restraining members such as end plates. Examples of the restraining method include, but are not limited to, a method that utilizes the restraining torque of a bolt.
[0018] The lithium ion battery of the present disclosure includes an electrode active material layer, and optionally further includes a current collector and an electrolyte layer.
[0019] <Electrode active material layer> The lithium ion battery of the present disclosure has, as an electrode active material layer, a negative electrode active material layer containing a negative electrode active material, and / or a positive electrode active material layer containing a positive electrode active material. The electrode active material layer containing a silicon clathrate electrode active material may be a positive electrode active material layer or a negative electrode active material layer, and is particularly a negative electrode active material layer. That is, in the present disclosure, the "silicon clathrate electrode active material" can be used as either a "positive electrode active material" or a "negative electrode active material", and is particularly used as a "negative electrode active material". In addition, the electrode active material layer optionally contains a solid electrolyte, a binder, and a conductive assistant.
[0020] (electrode active material) Silicon clathrate electrode active materials can be prepared by preparing a sodium silicon (NaSi) alloy and removing sodium from the NaSi alloy.
[0021] Specifically, a silicon source is reacted with a sodium source such as sodium hydride to prepare a NaSi alloy. The NaSi alloy thus prepared is then heated to remove sodium from the NaSi alloy and form a clathrate, thereby preparing a silicon clathrate electrode active material. Alternatively, the NaSi alloy thus prepared is reacted with aluminum fluoride as a sodium trapping agent to remove sodium from the NaSi alloy and form a clathrate, thereby preparing a silicon clathrate electrode active material.
[0022] When the silicon clathrate electrode active material is used as the negative electrode active material, the material of the positive electrode active material is not particularly limited. For example, the positive electrode active material can be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y Li-Mn spinel substituted with different elements, which has a composition represented by MyO4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn), and lithium titanate (Li x TiO y ), lithium metal phosphate (LiMPO4, M is one or more metals selected from Fe, Mn, Co, and Ni), and the like, but are not limited thereto.
[0023] The positive electrode active material may have a coating layer. The coating layer is a layer containing a substance that has lithium ion conductivity, is low in reactivity with the positive electrode active material and the solid electrolyte, and can maintain the shape of the coating layer without flowing even when it comes into contact with the active material and the solid electrolyte. Specific examples of materials constituting the coating layer include LiNbO3, Li4Ti5O 12 , Li3PO4, etc., but are not limited to these.
[0024] The shape of the positive electrode active material may be, for example, particulate. The average particle size (D50) of the positive electrode active material is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle size (D50) of the positive electrode active material is, for example, 50 μm or less, and may be 20 μm or less. The average particle size (D50) can be calculated, for example, from measurements using a laser diffraction particle size distribution meter or a scanning electron microscope (SEM).
[0025] (solid electrolyte) The material of the solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte for use in lithium ion batteries can be used. For example, the solid electrolyte may be a sulfide solid electrolyte.
[0026] Examples of sulfide solid electrolytes include, but are not limited to, sulfide amorphous solid electrolytes, sulfide crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.
[0027] The sulfide solid electrolyte may be a glass or a crystallized glass (glass ceramic).
[0028] When the electrode active material layer contains a solid electrolyte, the mass ratio of the electrode active material particles to the solid electrolyte in the electrode active material layer (mass of electrode active material particles:mass of solid electrolyte) is preferably 85:15 to 30:70.
[0029] (Conductive assistant) The conductive assistant is not particularly limited. For example, the conductive assistant may be VGCF (Vapor Grown Carbon Fiber), acetylene black (AB), Ketjen Black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto.
[0030] (binder) The binder is not particularly limited. For example, the binder may be a material such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), or styrene butadiene rubber (SBR), or a combination thereof, but is not limited thereto.
[0031] The thickness of the electrode active material layer is 55 μm or less. This thickness may be more than 0.0 μm, 1.0 μm or more, 2.0 μm or more, or 3.0 μm or more, and may be 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less.
[0032] In the lithium ion batteries of the present disclosure, the value of formula (A) is 2,000,000 or less. This value may be greater than 0, 10,000 or more, 20,000 or more, or 25,000 or more, and may be 1,900,000 or less, 1,800,000 or less, 1,700,000 or less, 1,600,000 or less, or 1,500,000 or less.
[0033] The charge amount of the silicon clathrate electrode active material may be 700mAh / g or more and 3,500mAh / g or less. The charge amount may be 800mAh / g or more, 900mAh / g or more, or 1,000mAh / g or more, and may be 3,000mAh / g or less, 2,500mAh / g or less, 2,000mAh / g or less, 1,750mAh / g or less, or 1,500mAh / g or less. The charge amount is a value measured when measuring the increase in the confining pressure, which is an index indicating the degree of expansion of the battery in this disclosure.
[0034] <Current collector> The material used for the negative electrode current collector is not particularly limited, and any material that can be used as a negative electrode current collector for a battery can be appropriately adopted. For example, the material may be copper, a copper alloy, or copper plated or vapor-deposited with nickel, chromium, carbon, or the like, but is not limited to these.
[0035] The shape of the negative electrode current collector is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.
[0036] The material used for the positive electrode current collector is not particularly limited, and any material that can be used as a positive electrode current collector for a battery can be appropriately adopted. For example, the material may be, but is not limited to, SUS, nickel, chromium, gold, platinum, aluminum, iron, titanium, zinc, etc., and these metals plated or vapor-deposited with nickel, chromium, carbon, etc.
[0037] The shape of the positive electrode current collector is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.
[0038] <Electrolyte layer> The electrolyte layer may be a solid electrolyte layer. The solid electrolyte layer includes at least a solid electrolyte. The solid electrolyte layer may include a binder or the like as necessary in addition to the solid electrolyte. For the solid electrolyte and the binder, the above description regarding the electrode active material of the present disclosure can be referred to.
[0039] The thickness of the solid electrolyte layer is, for example, 0.1 to 300 μm, and preferably 0.1 to 100 μm. EXAMPLES
[0040] Example of synthesis Synthesis of silicon clathrate electrode active material (alloying) A sodium silicon (NaSi) alloy was produced using silicon (Si) powder (Kojundo Kagaku, SIEPB32) with a crystalline structure and sodium hydride (NaH) as a sodium (Na) source. The NaH used was washed with hexane in advance. The NaH and Si powders were weighed out so that the molar ratio was 1.05:1, and the weighed NaH and Si powders were mixed in a cutter mill. The resulting mixture was heated in a heating furnace under an argon atmosphere at 400°C for 40 hours to obtain a powdered NaSi alloy.
[0041] (Clatification) The obtained NaSi alloy and aluminum fluoride (AlF3) particles were weighed to a molar ratio of 1:0.35, and the weighed NaSi alloy and AlF3 particles were mixed with a cutter mill to obtain a reaction raw material. The obtained powdered reaction raw material was placed in a stainless steel reaction vessel and reacted in a heating furnace under an argon atmosphere at 310°C for 60 hours to obtain a silicon clathrate. The obtained silicon clathrate was acid washed using a mixed solvent of HNO3 and H2O in a volume ratio of 10:90 to remove by-products in the reaction product. After washing, it was filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain a powdered silicon clathrate. Furthermore, the obtained silicon clathrate was washed with a 3wt% hydrogen fluoride (HF) solution, filtered, and then dried at 120°C for 3 hours or more to obtain silicon clathrate electrode active material particles.
[0042] Example 1 (Making a lithium-ion battery) (Preparation of negative electrode mixture) Butyl butyrate, a 5 wt% butyl butyrate solution of polyvinylidene fluoride (PVDF) binder, vapor grown carbon fiber (VGCF) as a conductive additive, silicon clathrate electrode active material of the synthesis example, and Li2S-P2S5 glass ceramic as a sulfide solid electrolyte were added to a polypropylene container, and the mixture was stirred for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT). Next, the container was shaken for 30 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.) to obtain a slurry-like negative electrode mixture (negative electrode mixture slurry).
[0043] (Formation of negative electrode active material layer) The obtained negative electrode composite slurry was applied onto a copper (Cu) foil serving as a negative electrode current collector by the blade method using an applicator, and then dried for 30 minutes on a hot plate heated to 100°C, thereby forming a negative electrode active material layer on the negative electrode current collector to a thickness of 33.2 μm.
[0044] (Formation of solid electrolyte layer) Heptane, a 5 wt% heptane solution of butylene rubber (BR)-based binder, and Li2SP2S5-based glass ceramic as a sulfide solid electrolyte were added to a polypropylene container and stirred for 30 seconds with an ultrasonic disperser (UH-50, manufactured by SMT Co., Ltd.). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.) to obtain a solid electrolyte slurry.
[0045] The obtained solid electrolyte slurry was applied onto an aluminum (Al) foil as a release sheet by a blade method using an applicator, and dried for 30 minutes on a hot plate heated to 100°C to form a solid electrolyte layer. Multiple solid electrolyte layers were produced.
[0046] (Preparation of Positive Electrode Mixture) A polypropylene container is filled with butyl butyrate, a 5 wt% butyl butyrate solution of a PVDF-based binder, and LiNi with an average particle size of 6 μm as the positive electrode active material. 1 / 3 Co 1 / 3 Mn 1 / 3O2, Li2S-P2S5-based glass ceramic as a sulfide solid electrolyte, and VGCF as a conductive additive were added to the container and stirred for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT Co., Ltd.). Next, the container was shaken for 3 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), further stirred for 30 seconds with the ultrasonic dispersion device, and shaken for 3 minutes with the shaker to obtain a slurry-like positive electrode mixture (positive electrode mixture slurry).
[0047] (Formation of Positive Electrode Active Material Layer) The obtained positive electrode composite slurry was applied onto an Al foil serving as a positive electrode current collector by a blade method using an applicator, and then dried for 30 minutes on a hot plate heated to 100°C, thereby forming a positive electrode active material layer on the positive electrode current collector.
[0048] (Battery Assembly) The positive electrode current collector, the positive electrode active material layer, and the first solid electrolyte layer were laminated in this order, and the laminate was set in a roll press and pressed at a pressure of 100 kN / cm and a temperature of 165° C. to obtain a positive electrode laminate.
[0049] The negative electrode current collector, the negative electrode active material layer, and the second solid electrolyte layer were laminated in this order, and the laminate was set in a roll press and pressed at a pressure of 60 kN / cm and a temperature of 25° C. to obtain a negative electrode laminate.
[0050] Furthermore, the Al foil as a release sheet was peeled off from the surfaces of the solid electrolyte layers of the positive electrode laminate and the negative electrode laminate, and then the Al foil as a release sheet was peeled off from the third solid electrolyte layer.
[0051] The positive electrode laminate and the negative electrode laminate were laminated on each other so that the solid electrolyte layer side of each laminate faced the third solid electrolyte layer, and the laminate was set in a flat uniaxial press and pre-pressed at 100 MPa and 25° C. for 10 seconds, and finally the laminate was set in a flat uniaxial press and pressed for 1 minute at a pressing pressure of 200 MPa and a pressing temperature of 120° C. In this way, the all-solid-state battery of Example 1 was obtained.
[0052] Examples 2 to 9 and Comparative Example 9 In the step of forming the negative electrode active material layer, the all-solid-state batteries of Examples 2 to 9 and Comparative Example 9 were obtained in the same manner as in Example 1, except that the thickness of the negative electrode active material layer was set as shown in Table 1.
[0053] Comparative Examples 1 to 8 The all-solid-state batteries of Comparative Examples 1 to 8 were obtained in the same manner as in Example 1, except that in the preparation step of the negative electrode composite, instead of the silicon clathrate electrode active material, Si powder having a crystalline structure (Kojundo Kagaku, SIEPB32) was used, and in the formation step of the negative electrode active material layer, the thickness of the negative electrode active material layer was set as shown in Table 1.
[0054] "evaluation" <Measurement of increase in confining pressure> The cell prepared using the restraining tool was restrained at a predetermined restraining pressure, and the increase in restraining pressure was measured when the cell was charged at a constant current and constant voltage up to 4.55 V at a 10-hour rate (1 / 10C). A large increase in the restraining pressure means a large expansion amount of the battery. The increase in the restraining pressure is the difference between the maximum and minimum values of the restraining pressure, and the values of the examples and comparative examples other than Comparative Example 1 are shown as relative values when the value of Comparative Example 1 is set to 100. The charge amount was also measured.
[0055] "result" The measurement results of the Si structure, the thickness of the electrode active material layer, the charge amount, the value of formula (A), and the increase in confining pressure are shown in Table 1 and FIG.
[0056] [Table 1]
[0057] As shown in Table 1 and FIG. 1, the batteries of the examples, which had an electrode active material layer having a thickness of 55 μm or less and containing a silicon clathrate electrode active material, and in which the value of formula (A) was 2,000,000 or less, had a smaller increase in confining pressure than the batteries of the comparative examples.
Claims
1. An electrode active material layer is provided, The thickness of the electrode active material layer is 55 μm or less, the electrode active material layer comprises a silicon clathrate electrode active material; and The following relationship is satisfied: Lithium-ion battery: (Thickness of the electrode active material layer (μm)) 2 × (charge amount (mAh / g) of the silicon clathrate electrode active material)≦2,000,000...(A).
2. 2. The lithium ion battery according to claim 1, wherein the electrode active material layer has a thickness of 35 μm or less.
3. 3. The lithium ion battery according to claim 1, wherein the charge capacity of the silicon clathrate electrode active material is 700 mAh / g or more and 3,500 mAh / g or less.
Citation Information
Patent Citations
Secondary cell and secondary cell system
JP2023098419A
Active material, negative electrode layer, battery and these manufacturing methods
JP2021158003A
Active material, negative electrode layer, battery and these manufacturing methods
JP2021158004A